MOTIVASI SISWA DALAM PEMBELAJARAN SENI BUDAYA DI KELAS X. BAHASA SMA PEMBANGUNAN UNP - Yolla Alvionella; Susmiarti Susmiarti; Yuliasma Yuliasma (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe the cause of the low level of motivation Factors about students in learning the art of dance in high school development. This type of research is qualitative research methods a descriptive analysis. The object of this research is the motivation of students in learning the art of dance in HIGH SCHOOL Language Class x. development of UNP. Type of data captured is the primary data and secondary data. The main instruments in the collection of data are observation, interview, writing instruments, camera. Data collection techniques used in this research is now done by observation and documentation, interviews, observations. The results showed that the lack of student learning motivation in high school art lesson on UNP Development dance. Factors that affect the motivation of high school students learning construction of UNP on the subjects of dance are internal factors namely still less his perseverance in learning students in the task given by the teachers, there are still students When told to appear unwilling students flits, still a lack of awareness of students in asking if diberii the opportunity of learning the art of dance, and external factors i.e., classroom management, infrastructure. Keywords: Student Motivation, learning the art of Dance